2016
DOI: 10.3390/polym8060234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Very High Charge Density and Monomer Constitution on the Synthesis and Properties of Cationic Polyelectrolytes

Abstract: Abstract:The free-radical homopolymerization of 1,3-bis(N,N,N-trimethylammonium)-2-propylmethacrylate dichloride (di-M) and 1,3-bis(N,N,N-trimethylammonium)-2-propylacrylate dichloride (di-A) in aqueous solution yields cationic polyelectrolytes (PEL) with theoretical/structural charge spacing of only «0.12 nm. The high charge density causes condensation of «82% of the chloride counterions. The high level of counterion condensation reduces the ionic strength in the polymerizing batch when the monomer molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“…Thus, the extent of counterion condensation increases with conversion and total monomer content, in agreement with observations made in a study of poly(vinylbenzyltrialkylammonium) that revealed a significant effect of both polyelectrolyte concentration and polymer chain length on polyion–counterion interaction 39. Recent studies by Ahmadloo et al on the radical homopolymerization of two doubly charged cationic monomers in aqueous solution concluded that high charge density results in high counterion condensation (≈82%), thereby greatly reducing the ionic strength of the polymerizing batch 31. The level of condensation (≈30%) is much lower for 10 wt% TMAEMC in solution, an indication that the influence of free counterions remain important throughout the polymerization.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Thus, the extent of counterion condensation increases with conversion and total monomer content, in agreement with observations made in a study of poly(vinylbenzyltrialkylammonium) that revealed a significant effect of both polyelectrolyte concentration and polymer chain length on polyion–counterion interaction 39. Recent studies by Ahmadloo et al on the radical homopolymerization of two doubly charged cationic monomers in aqueous solution concluded that high charge density results in high counterion condensation (≈82%), thereby greatly reducing the ionic strength of the polymerizing batch 31. The level of condensation (≈30%) is much lower for 10 wt% TMAEMC in solution, an indication that the influence of free counterions remain important throughout the polymerization.…”
Section: Resultssupporting
confidence: 86%
“…While previous studies provide insights on the effects of counterions on the final properties of PELs in dilute solution,31,40 little is known about the solution properties at the higher concentrations of PELs associated with polymerization 35. Thus, conductivity and counterion concentrations of non‐reacting solutions were measured at ambient temperatures to investigate the changes that occur during transition from a monomer to a polymer solution in batch polymerization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations